Effect of Photoperiod on Haematological Parameters of Surti Does and Kids - Padheriya, Yogesh D.; Singh, Rana Ranjeet; Chaudhary, Sandhya S.; Patel, Navin B. (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
Effect of artificial long-day photoperiod under tropical climate was limited and no such reports were available for Surti goats and kids. Therefore, the present study was undertaken to know the effect of photoperiod on monthly haematological parameters of 24 parturient does and their kids for 5 months. The animals were divided into four groups after their parturition/ birth and were subjected to photoperiodic treatment. Control (n=6 does and kids, natural photoperiod, 11.5 h light : 12.5 h darkness) group, T1 (n=6 does and kids, 14 h light : 10 h darkness) group, T2 (n=6 does and kids, 16 h light : 08 h darkness) group and T3 (n=6 does and kids, 08 h light : 16 h darkness) group. Blood samples were collected at monthly interval during entire experimental period. Positive effect of long-day photoperiod treatment was observed on haemoglobin and total erythrocyte count. However, the PCV % and total leukocyte count was significantly higher in short day photoperiod.